FACTORS AFFECTING THE IMPLEMENTATION OF SETARA DARING PLATFORM-BASED LEARNING AT SKB 2 SAMARINDA - Veralion, Triska Rahayu; Saraka, Saraka; Winarti, Hepy Tri; Mustangin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This study aims to analyze the factors that influence the success of the implementation of equality education learning using seTARA daring. This research approach was carried out using a qualitative approach. Qualitative research in this study is in accordance with the purpose of the study, which is to examine in depth the factors that affect the success of the implementation of equality education learning using online education. Descriptive research in this study to describe the research findings. Data collection methods in this study using interviews, observations and document study methods. Interviews were conducted with interactions between researchers and research informants. The research informants are Equality Education Tutors, Equality Education Students, and the Head of SPNF SKB 2 Samarinda. Data analysis using data reduction, data presentation, and conclusions. Data validity checking techniques are implemented by source triangulation and triangulation techniques. The results showed that the factor that influenced the successful process of implementing learning using seTARA daring, in this study was equality education educators who had technological competence. Diverse learners include students who have a busy life that affects the learning process. Adequate learning facilities at SPNF SKB 2 Samarinda also affect the success of learning implementation.